Male involvement in family planning use and its determinants in Ethiopia: a systematic review and meta-analysis protocol - Etsay Woldu Anbesu; Setognal Birara Aychiluhm; Zinabu Hadush Kahsay (Systematic Reviews, 2022)
Abstract Background The need to include males who require joint spousal decisions is critical in achieving key reproductive health indicators. Low involvement of males in family planning use is one of the contributing factors for low contraceptive use in Ethiopia. Despite this, there are inconsistent findings on the prevalence and determinants of male involvement in family planning use in Ethiopia. Thus, this systematic review and meta-analysis aimed to determine the pooled prevalence of male involvement in family planning use and its determinants in Ethiopia. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines will be used to develop the protocol. The online databases PubMed, CINAHL, Google Scholar, and unpublished gray literature will be searched to retrieve available articles from April 10 to August 11, 2021. The two authors will conduct selection of studies, data extraction, and quality assessment. The quality of the studies will be assessed using the Joanna Briggs Institute checklist. The chi-squared test and I-squared statistic will be used to examine heterogeneity among studies. Sources of heterogeneity will be investigated using subgroup analysis and meta-regression based on regions and residence (urban and rural). Publication bias will be examined by observation using funnel plots and statistically by Begg’s and Egger’s tests. A random-effects model will be used to estimate the pooled prevalence and its determinants of male involvement in family planning use. Discussion The role of males in family planning and participation in contraceptive use improves women’s uptake and continuity of family planning use. Although there are studies on male involvement in family planning use, there are no synthesis research findings on the pooled prevalence of male involvement in family planning use and its determinants in Ethiopia. Therefore, the findings from this systematic review and meta-analysis will help the national health sector transformational plane emphasize the pooled prevalence and its determinants that drive low male involvement in family planning use in Ethiopia.